2013
DOI: 10.1161/atvbaha.112.300527
|View full text |Cite
|
Sign up to set email alerts
|

Lipid Phosphate Phosphatase 3 Negatively Regulates Smooth Muscle Cell Phenotypic Modulation to Limit Intimal Hyperplasia

Abstract: Rationale The lipid phosphate phosphatase 3 (LPP3) degrades bioactive lysophospholipids including lysophosphatidic acid (LPA) and sphingosine-1-phosphate (S1P) and thereby terminates their signaling effects. While emerging evidence links LPA to atherosclerosis and vascular injury responses, little is known about the role of vascular LPP3. Objective The goal of this study was to determine the role of LPP3 in the development of vascular neointima formation and smooth muscle cells (SMC) responses. Methods and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
52
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
7
2

Relationship

4
5

Authors

Journals

citations
Cited by 46 publications
(53 citation statements)
references
References 42 publications
1
52
0
Order By: Relevance
“…However, available data indicate that the risk-associated PPAP2B allele predicts lower mRNA expression in blood cells. Inactivation of the PPAP2B gene in vascular smooth muscle cells leads to exaggerated neointima formation in response to arterial injury in vivo and enhanced migration, proliferation, and differentiation responses of cultured vascular smooth muscle cells to LPA in vitro ( 15 ). These observations support the idea that PPAP2B is normally protective against at least the vascular smooth muscle cell mediated component of experimental atherothrombotic disease.…”
supporting
confidence: 68%
“…However, available data indicate that the risk-associated PPAP2B allele predicts lower mRNA expression in blood cells. Inactivation of the PPAP2B gene in vascular smooth muscle cells leads to exaggerated neointima formation in response to arterial injury in vivo and enhanced migration, proliferation, and differentiation responses of cultured vascular smooth muscle cells to LPA in vitro ( 15 ). These observations support the idea that PPAP2B is normally protective against at least the vascular smooth muscle cell mediated component of experimental atherothrombotic disease.…”
supporting
confidence: 68%
“…It has been reported that LPA promotes hepatocyte secretion of apoBcontaining proteins ( 12 ) and it is possible that some of the changes noted here may be due to changes in plasma LPA levels acting on the liver. Regardless of the mechanism(s) the data presented here further add to the growing body of evidence suggesting that LPA plays a major role in lipid metabolism, infl ammation, and atherosclerosis ( 7,(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21).…”
Section: Discussionmentioning
confidence: 59%
“…In vivo in LDLR Ϫ / Ϫ mice, it was shown that application of a collar to the carotid artery resulted in a time-dependent increase in artery LPA levels ( 18 ). Also in vivo, mice with selective inactivation of lipid phosphate phosphatase 3 displayed an exaggerated neointimal response to injury ( 19 ). The gene for lipid phosphate phosphatase 3 was identifi ed as a susceptibility locus for coronary artery disease ( 20 ).…”
mentioning
confidence: 99%
“…In ECs, PPAP2B localizes to adherens junctions and regulates ␤ -catenin signaling, thereby affecting cell migration ( 34 ). In SMCs, it regulates lysophospholipid signaling responses and affects SMC phenotypic plasticity ( 35 ). Our results indicate that PPAP2B may be involved in susceptibility to atherosclerosis via its dual function in vascular wall cells.…”
Section: Discussionmentioning
confidence: 79%